Deep Structure of the Grenada Basin From Wide‐Angle Seismic, Bathymetric and Gravity Data. Issue 2 (16th February 2021) - Padron, Crelia; Klingelhoefer, Frauke; Marcaillou, Boris; Lebrun, Jean‐Frédéric; Lallemand, Serge; Garrocq, Clément; Laigle, Mireille; Roest, Walter R; Beslier, Marie‐Odile; Schenini, Laure; Graindorge, David; Gay, Aurelien; et al.
Abstract: The Grenada back‐arc basin is located between the Aves Ridge, which hosted the remnant Early Paleogene "Great Caribbean Arc, " and the Eocene to Present Lesser Antilles Arc. Several earlier studies have proposed different modes of back‐arc opening for this basin, including N‐S and E‐W directions. The main aim of this study is to constrain the circumstances leading to the opening of the basin. Three combined wide‐angle and reflection seismic profiles were acquired in the Grenada basin. The final velocity models from forward travel time and gravity modeling image variations in thickness and velocity structure of the sedimentary and crustal layers. The sedimentary cover has a variable thickness between 1 km on top of the ridges to ∼10 km in the basin. North of Guadeloupe Island, the crust is ∼20 km thick without significant changes between Aves Ridge, the Grenada basin, and the Eocene and present Lesser Antilles arc. South of Guadeloupe Island the Grenada basin is underlain by a oceanic crust of mainly magmatic origin over a width of ∼80 km. Here, the western flank of the Lesser Antilles Arc, the crust is 17.5‐km thick. The velocity structure of the Lesser Antilles Arc is typical of volcanic arcs or oceanic plateaus. West of the basin, the crust thickens to 25 km at Aves Ridge in an 80–100 km wide arc‐ocean transition zone. The narrowness of this transition zone suggests that opening might have proceeded in a direction oblique to the main convergence. Opening probably was accompanied by moderate volcanism. Plain Language Summary: In this study, we investigated the formation of the Grenada Basin, located west of the Lesser Antilles island arc. These types of basins typically open behind subduction zones, where one tectonic plate is moving underneath another plate. We deployed instruments on the seafloor to record acoustic signals made using pressured air in an array towed behind the ship. This method allowed us to image the sediments and crustal layers along the three profiles of our study. We find that the structure of both the eastern and western margin of the basin are similar in their physical properties, that volcanism was widespread during basin opening, and the southeastern part of the basin is underlain by crust typically found in oceans. More research is needed to explore the direction of opening and the extent of the oceanic‐type crust underneath the modern island arc. Key Points: Wide‐angle and gravity data were acquired along three profiles in the Grenada basin during the GARANTI cruise in 2017 Crustal thickness at Aves ridge and the Lesser Antilles arc is between 21 and 27 km and velocities are compatible with other volcanic arcs A 80‐km‐wide region in the south of the basin is underlain by oceanic crust